Liquid health: medicine in the age of surveillance capitalism - Rubeis, Giovanni (Social science & medicine, 2023)
Digital health technologies transform practices, roles, and relationships in medicine. New possibilities for a ubiquitous and constant data collection and the processing of data in real-time enable more personalized health services. These technologies might also allow users to actively participate in health practices, thus potentially changing the role of patients from passive receivers of healthcare to active agents. The crucial driving force of this transformation is the implementation of data-intensive surveillance and monitoring as well as self-monitoring technologies. Some commentators use terms like revolution, democratization, and empowerment to describe the aforementioned transformation process in medicine. The public debate as well as most of the ethical discourse on digital health tends to focus on the technologies themselves, mostly ignoring the economic framework of their design and implementation. Analyzing the transformation process connected to digital health technologies needs an epistemic lens that also considers said economic framework, which I argue is surveillance capitalism. This paper introduces the concept of liquid health as such an epistemic lens. Liquid health is based on Zygmunt Bauman's framing of modernity as a process of liquefaction that dissolves traditional norms and standards, roles, and relations. By using liquid health as an epistemic lens, I aim to show how digital health technologies reshape concepts of health and illness, change the scope of the medical domain, and liquify roles and relationships that surround health and healthcare. The basic hypothesis is that although digital health technologies can lead to personalization of treatment and empowerment of users, their economic framework of surveillance capitalism may undermine these very goals. Using liquid health as a concept allows us to better understand and describe practices of health and healthcare that are shaped by digital technologies and the specific economic practices they are inseparably attached to.